Kapit-Komunidad reinforcing the elderly's social role and memory cognition through a dementia-friendly community center - Vardeleon, Paul Yvan M.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The rapidly aging population presents significant challenges worldwide, particularly in addressing the social roles and vulnerabilities of older adults, who are at an increased risk of developing dementia, one of the leading causes of disability. In the Philippine context, societal stigma often portrays the elderly as inherently frail and cognitively impaired, reinforcing a direct and negative association with dementia. This stigma, coupled with limited access to care, exacerbates the difficulties faced by the elderly, particularly those from low- to middle-income households. Existing dementia care models in the country remain fragmented and predominantly institutional, often requiring the elderly to be uprooted from their communities, further contributing to isolation and marginalization. In contrast, countries like Singapore have successfully integrated dementia care into their broader urban environments through community-based dementia-friendly communities. These models empower persons living with dementia (PLWDs) while actively engaging the public in their care, creating inclusive spaces that support the elderly both physically and socially. This study explored the potential application of such a model in the Philippines, focusing on the design of a dementia-friendly community center in Marikina City. The proposed approach integrates spatial and design strategies aimed at elderly empowerment, cognitive health, and societal integration. By fostering an inclusive and supportive environment, the research seek to support memory cognition, empower older adults, and promote community participation. Ultimately, the study advocates for the adoption of a community-based dementia care model as a comprehensive, sustainable, and culturally sensitive dementia care in the Philippines.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Dementia -- Marikina City; Community -- Mental Health Services -- Marikina City; Dementia -- Social aspects; Dementia -- Patients -- Care; Cognitive impairment; Dementia-friendly environments